Structural and electrical properties of (x)Mn0.45Ni0.05Zn0.50Fe2O4 + (1 − x)BaZr0.52Ti0.48O3 multiferroic materials - Azizar Rahman, M; Kumar Saha, Sonet; Akther Hossain, A K M (Materials research express, 2014)
Multiferroic (x)Mn0.45Ni0.05Zn0.50Fe2O4 + (1 − x)BaZr0.52Ti0.48O3 materials (where x varies from 0.0 to 0.8 in steps of 0.20) were prepared by the standard solid state reaction method. X-ray diffraction patterns verify the development of tetragonal perovskite structure for ferroelectric and cubic spinel structure for ferrite phase. The frequency and temperature dependent electrical parameters have been investigated to understand the conduction mechanism in these multiferroic materials. The grain effect contributes to the conduction mechanism for the sample containing 0-60% ferrite and both the grain and grain boundary effect contribute to the conduction mechanism for the composite containing 80% ferrite at high temperature. The ac conductivity increases with increasing frequency for the sample x = 0. This is due to the small polaron hopping. For the sample containing 20% ferrite, the frequency independent dc conductivity is observed at low temperature and dominates over a wide frequency range at high temperature region for the sample containing higher percentage of ferrite. The frequency independent dc conductivity is shifted to the frequency dependent ac conductivity, indicating the beginning of the conductivity relaxation phenomenon. This is attributed to the translation of long range polaron hopping to the small range charge carriers. The temperature dependence conductivity indicates that the impurities present in these multiferroic materials are almost minimized and polaron hopping type of conduction mechanism is valid.